Oral behaviors in Chinese temporomandibular disorder patients: insights from exploratory and confirmatory factor analyses - Liu, Tiqian; Yap, Adrian Ujin; Sun, Yanyu; Zheng, Yunhao; Wang, Tianqi; Zeng, Shiya; Liu, Zhen; Xiong, Xin (Frontiers in Neurology, 2024)
AimThis study aimed to evaluate the factor structure of the Oral Behaviors Checklist (OBC) in Chinese temporomandibular disorder (TMDs) patients and compare the outcomes with those of Western patients. Additionally, it examined the correlations between different OBC subscale scoring methods.MethodsA total of 869 patients completed a survey that included demographic information, the Symptom Questionnaire, and OBC. This was followed by a clinical examination and diagnosis based on the Diagnostic Criteria for TMDs (DC/TMDs). Exploratory factor analysis, along with confirmatory factor analysis, was applied to waking-state oral behaviors, revealing two key factors: Chinese non-functional (C-NFA) and functional (C-FA) oral activities. Items were contrasted with those of Italian TMDs patients (I-NFA and I-FA), and subscale scores were computed, compared, and correlated using Kruskal Wallis and Post-hoc and Spearman’s rank-order correlation (α = 0.05).ResultsVariations in NFA and FA items were observed between Chinese and Italian TMDs patients. For both NFA scoring methods, significant differences were noted between pain-related and intra-articular TMDs. The C-NFA and I-NFA, as well as C-FA and I-FA, scoring methods yielded scores with strong correlations (r > 0.8).ConclusionNFA and FA subscale items were determined for Chinese TMDs patients. Despite item discrepancies, C-NFA and C-FA scores were strongly correlated with I-NFA and I-FA scores, respectively. The OBC can be effectively simplified for use with Chinese TMDs patients. Developing and validating an East–West short-form version of the OBC should be prioritized, given the variations in oral behaviors across countries and cultures.